Establishment and validation of the cut-off values of estimated glomerular filtration rate and urinary albumin-to-creatinine ratio for diabetic kidney disease: A multi-center, prospective cohort study - Gao, Zhongai; Zhu, Yanjuan; Sun, Xiaoyue; Zhu, Hong; Jiang, Wenhui; Sun, Mengdi; Wang, Jingyu; Liu, Le; Zheng, Hui; Qin, Yongzhang; Zhang, Shuang; Yang, Yanhui; et al. (Frontiers in Endocrinology, 2022)
Objective We aimed to study the cut-off values of estimated glomerular filtration rate (eGFR) and the urinary albumin creatinine ratio (UACR) in the normal range for diabetic kidney disease (DKD). Methods In this study, we conducted a retrospective, observational cohort study included 374 type 2 diabetic patients who had baseline eGFR ≥60 mL/min/1.73 m2 and UACR <30 mg/g with up to 6 years of follow-up. The results were further validated in a multi-center, prospective cohort study. Results In the development cohort, baseline eGFR (AUC: 0.90, cut-off value: 84.8 mL/min/1.73 m2, sensitivity: 0.80, specificity: 0.85) or UACR (AUC: 0.74, cut-off value: 15.5mg/g, sensitivity: 0.69, specificity: 0.63) was the most effective single predictor for DKD. Moreover, compared with eGFR or UACR alone, the prediction model consisted of all of the independent risk factors did not improve the predictive performance (P >0.05). The discrimination of eGFR at the cut-off value of 84.80 mL/min/1.73 m2 or UACR at 15.5mg/g with the largest Youden’s index was further confirmed in the validation cohort. The decrease rate of eGFR was faster in patients with UACR ≥15.5mg/g (P <0.05). Furthermore, the decrease rate of eGFR or increase rate of UACR and the incidence and severity of cardiovascular disease (CVD) were higher in patients with eGFR ≤84.8 mL/min/1.73 m2 or UACR ≥15.5mg/g (P <0.05). Conclusions In conclusion, eGFR ≤84.8mL/min/1.73 m2 or UACR ≥15.5mg/g in the normal range may be an effective cut-off value for DKD and may increase the incidence and severity for CVD in type 2 diabetic patients.